On the impact of inequality on growth, human development, and governance - Ines A. Ferreira; Rachel M. Gisselquist; Finn Tarp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
Countering recent rises in many countries of inequality in income and wealth is widely recognized as a major development challenge. This is so from an ethical perspective and because greater inequality is perceived to be detrimental to key development aims. Still, an informed debate on the effects of inequality requires clear evidence. This review contributes to the literature by taking stock and providing an overview of current knowledge of the impact of income inequality on three important outcomes: economic growth, health and education as two dimensions of human development, and governance, with a focus on democracy. Drawing on the insights from different disciplines and considering recent work, it reveals that existing evidence provides somewhat mixed results and argues for a need for further in-depth empirical work. It also points to explanations for the lack of consensus embedded in data quality and availability, measurement issues, and the shortcomings of the different methods employed. Finally, we point to promising future research avenues relying on experimental work for micro level analysis, more region- and country-specific studies, and reiterate the need for improvements in the availability and reliability of data.
Keywords: O15; O40; P48; 330; inequality; growth; health; education; governance; review